Konsep Ketuhanan dalam Filsafat Erich Fromm (1900-1980) - Krisna Suksma Yogiswari (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Fluctuations in the concept of God throughout the course of human life always occur. Erich Fromm (1900-1980) who was a psychoanalyst of the Frankfrut School, in his works implicitly characterized a concept he called himself 'Non-Theistic Mysticism' as a form of humanist spirituality and overcame human separateness, in terms of Fromm called ' well being 'as a consequence of its existence, which can finally overcome the human dilemma and diversity. This study is an attempt to outline the understanding of God in the perspective of Erich Fromm, as well as God's and human relations.